(untitled) - Josenilson Antônio da Silva; Kleyton de Carvalho Mesquita; Ana Carolina de Souza Machado Igreja; Isabella Cristina Rodrigues Naves Lucas; Aline Ferreira Freitas; Sandra Maximiano de Oliveira; Izelda Maria Carvalho Costa; Iphis Tenfuss Campbell (Sociedade Brasileira de Dermatologia, 2013)
The skin often signals systemic changes. Some neoplastic diseases that affect internal organs may trigger several cutaneous manifestations. Although these dermatoses are relatively unusual, the recognition of some typical paraneoplastic dermatoses may lead to the early diagnosis of a neoplasm and determine a better prognosis. In this review article, we discuss the paraneoplastic cutaneous manifestations strongly associated with neoplasms, which include acanthosis nigricans maligna, tripe palms, erythema gyratum repens, Bazex syndrome, acquired hypertrichosis lanuginosa, necrolytic migratory erythema, Leser-Trélat sign and paraneoplastic pemphigus. We also review the clinical manifestations of each condition and include updated knowledge on disease pathogenesis. A pele é, muitas vezes, reflexo de manifestações sistêmicas. Doenças neoplásicas que afetam órgãos internos podem exibir manifestações cutâneas diversas. Apesar de relativamente incomuns, o reconhecimento de dermatoses paraneoplásicas pode levar ao diagnóstico precoce da neoplasia e, consequentemente, determinar melhor prognóstico. Nesta revisão serão discutidas as manifestações cutâneas paraneoplásicas com maior força de associação a neoplasias, que incluem acantose nigricante maligna, paquidermatoglifia adquirida, erythema gyratum repens, síndrome de Bazex, hipertricose lanuginosa adquirida, eritema necrolítico migratório, sinal de Leser-Trélat e pênfigo paraneoplásico. Para cada condição serão revisadas e atualizadas as manifestações clínicas, principais neoplasias associadas e etiopatogenia.